Pengaruh Campuran Metanol Dengan Bahan Bakar Premium Terhadap Viskositas Kinematis Dan Total Base Number Pelumas SAE10W-40 Pada Yamaha Lexi 125 CC - Prakasa, Mordekhai Yudha; Ghurri, Ainul; Nindhia, Tjokorda Gde Tirta (Teknik Desain Mekanika, 2021)
Abstract The use of motorized vehicles is increasingly causing a fossil fuel crisis. This crisis arises because the process of forming fossil fuels takes a long time. Seeing this situation, alternative fuels are needed to replace fossil fuels. The solution uses methanol as an alternative fuel. The type of fuel used in motor vehicles affects the characteristics of the motor vehicle lubricating oil used. In order to keep the vehicle engine performance in good condition, it is necessary to check the condition of the lubricant in terms of viscosity and the total base number contained in the lubricant. This study aims to determine the effect of a mixture of methanol and premium as a fuel for Yamaha Lexi 125 CC motorcycles on the viscosity and total base number of SAE10W-40 lubricant. The fuel used as research material is Pertamax and a premium blend of methanol, namely M15 and M20. The mileage used for each fuel is 2000 kilometers with the same lubricant, namely SAE10W 40. The test results show that the smallest decrease in kinematic viscosity is obtained when using M15 fuel of 38.59 centistoke and the smallest decrease in total base number is obtained when using the fuel. Pertamax burn is 0.71 mg KOH/g. Keywords: Methanol, viscosity and total base number